The neurobiology of ticklishness - Shimpei Ishiyama (Neuroscience Research, 2025)
Ticklishness is an idiosyncratic form of touch observed in multiple animal species, including humans. Although commonly regarded as trivial, it involves complex neurobiological mechanisms and diverse behavioral phenomena observed across species. Two distinct forms exist: knismesis, a mild tingling sensation elicited by gentle touch, and gargalesis, an intense sensation associated with involuntary laughter. Advocating the importance of clearly distinguishing these two types of ticklishness, this review synthesizes current knowledge on their neuronal underpinnings. Topics include somatosensory processing, self-tickling and sensory attenuation, emotional modulation, sociosexual dimensions, and evolutionary perspectives, among others. Special attention is given to the ambivalent nature of gargalesis, challenging conventional single-dimensional models of emotional valence. Ultimately, studying ticklishness provides a valuable opportunity to investigate playful emotional experiences from a naturalistic perspective, addressing fundamental yet underrepresented questions in contemporary neuroscience. Far from trivial, ticklishness thus provides valuable insights into the neural mechanisms underlying complex, context-dependent emotional and social experiences.